2016
DOI: 10.1002/nau.23112
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin increases perception of bladder filling in a forced diuresis experiment

Abstract: Aims:To study bladder sensation during a forced diuresis protocol and to assess differences in sensation perceived by different ethnic groups and after drinking artificially sweetened water. Methods:Female Caucasian and south Indian Asian volunteers performed the diuresis protocol drinking water, or water sweetened with saccharine (5 mg/kg body weight). Participants recorded filling sensation every 5 minutes while drinking 250-350 ml/15 minutes. They were asked to record the strongest sensation before voiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Diet cola 30 and saccharin-sweetened water 32 intake showed similar UV, 30,32 UNa + , 30 and UK +30 excretion patterns to still water in humans.…”
Section: Sugar Substitutes/sweetenersmentioning
confidence: 78%
“…Diet cola 30 and saccharin-sweetened water 32 intake showed similar UV, 30,32 UNa + , 30 and UK +30 excretion patterns to still water in humans.…”
Section: Sugar Substitutes/sweetenersmentioning
confidence: 78%
“…There were reports on the carcenogenic properties of saccharin and risk of development of cancer of the urinary bladder, but further studies disproved this (Weihrauch & Diehl, 2004;Vasconcelos et al, 2017). Non-calory sweeteners stimulate the development of intolerance of glucose by change in the microflora of the intestines and subsequent development of inflammatory processes in the organs (Suez et al, 2014;Nettleton et al, 2016;Qin, 2016;Bian et al, 2017b), and significantly reduce the sense of taste (Bakali et al, 2016;Sclafani & Ackroff, 2017;Dess et al, 2017;Choo & Dando, 2018). Despite these data, nowadays, saccharin is approved for ubiquitous usage in over 90 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, urine may play roles in human health beyond waste excretion. Anecdotal reports suggest that lower urinary tract symptoms (LUTS) such as frequency, urgency and pain/discomfort vary considerably during the course of a day and may be provoked by certain types of fluids, food, and circumstances that alter urine composition . For example, some IC/BPS patients have reported that symptoms improve with increased water intake and/or after elimination of specific fluids and foods from their diet.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal reports suggest that lower urinary tract symptoms (LUTS) such as frequency, urgency and pain/discomfort vary considerably during the course of a day and may be provoked by certain types of fluids, food, and circumstances that alter urine composition. 12 For example, some IC/BPS patients have reported that symptoms improve with increased water intake and/or after elimination of specific fluids and foods from their diet. Variability in IC/BPS patients' pain symptoms appears to correlate with urinary concentration, and conversely, may be relieved by urinary dilution, 13,14 but apparently not by ingestion of acidic foods when presented blindly to study participants.…”
Section: Introductionmentioning
confidence: 99%